Changes in hepatic phosphoprotein levels in mice infected with plasmodium berghei - Pramila Maniam,; Zainal Abidin Abu Hassan,; Noor Embi,; Hasidah Mohd Sidek, (Universiti Kebangsaan Malaysia, 2012)
Hepatic phosphoprotein levels are altered in mouse liver as a manifestation of bacteria, virus or parasite infection. Identification of signaling pathways mediated by these hepatic proteins contribute to the current understanding of the mechanism of pathogenesis in malarial infection. The present study was undertaken to evaluate the changes in hepatic phosphoprotein levels during Plasmodium berghei infection. Our study revealed changes in levels of three hepatic phosphoproteins following P. berghei infection compared to non-infected controls. Peptide fragment sequence analysis using tandem mass spectrometry (MS/MS) showed these hepatic proteins to be homologs to haemoglobin beta (HBB), class Pi glutathione S-tranferase (GSTPi) and carbonic anhydrase III (CAIII) proteins of Mus musculus species respectively from the NCBInr sequence database. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis predicted the involvement of these proteins in specific pathways in Mus musculus species; GSTPi in glutathione and drug metabolism and CAIII in nitrogen metabolism. This shows that P. berghei infection affects similar signaling pathways as those reported in other pathogenic infections such as that related to GSTPi and CAIII in response to oxidative stress.